HUBUNGAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT DENGAN MODEL PEMBELAJARAN COOPERATIVE SQ3R TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Tulloh, Hidaya (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2016)
Abstrak The purpose of this study is to determine the difference in average math student learning outcomes among students given SCRIPT kooepratif learning model with average math student learning outcomes given SQ3R cooperative learning model in the subject matter fractions. This type of research is an experimental research. The population in this study were all fourth grade students with a number of 48 students, divided into two (2) classes of IV.A class consists of 24 students, the class consists of 24 students IV.B. The sample / subject of study consisted of two groups, where the sample collection technique using cluster random sampling.The sample group in this study, namely, the first group is called the experimental group (class IV.A) and a second group called dick class (class IV.B). the results of this study can be concluded that the results of students' mathematics learning gained through cooperative methods script by 65.92% higher than the average mathematics learning outcomes obtained through methods cooperatif SQ3R by 54.25% on a subject matter fractions. Key words: Cooperative learning, learning outcomes, mathematics, SCRIPT,SQ3R.